Comparison of the Novel Immunocatch Legionella Test with Sofia Legionella FIA Assay and with BinaxNOW Legionella Card Assay for Detection of Legionella pneumophila (Serogroup 1) Antigen in Urine Samples - Congestrì, F. (J Clin Microbiol, 2019)
Legionnaires’ disease (LD) refers to a serious form of acute pneumonia caused by Legionella species. LD can be difficult to diagnose because the signs and symptoms are nonspecific, and therefore a rapid laboratory diagnosis is of paramount importance. In this study, a recently introduced immunochromatographic test (Immunocatch Legionella; Eiken Chemical Co., Ltd.) for Legionella pneumophila (serogroup 1) urinary antigen detection was compared with the Sofia Legionella fluorescent immunoassay (FIA) (Quidel) (routinely used in our laboratory) and with the widely used BinaxNOW Legionella assay (Alere). A total of 248 urine samples (60 frozen and 188 fresh) were evaluated. All of the samples were collected from patients with high clinical suspicion of Legionnaires’ disease. The three assays were performed simultaneously according to the manufacturers’ instructions. A total of 180 concordant negative and 66 concordant positive results were obtained. Only 2 discrepant results were registered. The sensitivity and specificity of Immunocatch compared with Sofia were, respectively, 98.5% and 99.4%. Cohen's kappa coefficient and overall percent agreement between Immunocatch and Sofia were also calculated and resulted in, respectively, 0.97 and 99.2%. These performances suggest that the Immunocatch test is a useful tool for Legionella pneumophila (serogroup 1) urinary antigen detection.